2021
DOI: 10.1242/dev.188631
|View full text |Cite
|
Sign up to set email alerts
|

A landmark-free morphometrics pipeline for high-resolution phenotyping: application to a mouse model of Down syndrome

Abstract: Characterising phenotypes often requires quantification of anatomical shape. Quantitative shape comparison (morphometrics) traditionally uses manually located landmarks and is limited by landmark number and operator accuracy. Here, we apply a landmark-free method to characterise the craniofacial skeletal phenotype of the Dp1Tyb mouse model of Down syndrome and a population of the Diversity Outbred (DO) mouse model, comparing it with a landmark-based approach. We identified cranial dysmorphologies in Dp1Tyb mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 67 publications
(81 reference statements)
10
59
0
Order By: Relevance
“…Analysis of skeletal structures showed that Dp1Tyb mice have reduced bone density, shorter tibia and altered craniofacial structures, in particular brachycephaly, all of which are typical of DS ( Baptista et al, 2005 ; Costa et al, 2018 ; Herrera et al, 2020 ; LaCombe and Roper, 2020 ; Vicente et al, 2020 ). In agreement with this, Dp1Tyb mice have shorter body and femur length ( Thomas et al, 2020 ), smaller crania and mandibles, mid-facial hypoplasia and cranial doming ( Toussaint et al, 2021 ). Similar craniofacial changes have been seen in the Dp1Yey mouse strain ( Starbuck et al, 2014 ; Takahashi et al, 2020 ), which, like Dp1Tyb mice, was generated by Cre/loxP chromosome engineering and has an extra copy of the same Hsa21-orthologous genes as Dp1Tyb ( Li et al, 2007 ).…”
Section: Discussionsupporting
confidence: 70%
“…Analysis of skeletal structures showed that Dp1Tyb mice have reduced bone density, shorter tibia and altered craniofacial structures, in particular brachycephaly, all of which are typical of DS ( Baptista et al, 2005 ; Costa et al, 2018 ; Herrera et al, 2020 ; LaCombe and Roper, 2020 ; Vicente et al, 2020 ). In agreement with this, Dp1Tyb mice have shorter body and femur length ( Thomas et al, 2020 ), smaller crania and mandibles, mid-facial hypoplasia and cranial doming ( Toussaint et al, 2021 ). Similar craniofacial changes have been seen in the Dp1Yey mouse strain ( Starbuck et al, 2014 ; Takahashi et al, 2020 ), which, like Dp1Tyb mice, was generated by Cre/loxP chromosome engineering and has an extra copy of the same Hsa21-orthologous genes as Dp1Tyb ( Li et al, 2007 ).…”
Section: Discussionsupporting
confidence: 70%
“…Finally, we compared the normalized centroid size, or centroid size divided by the number of landmarks for each method (Toussaint et al, 2021). Centroid size was calculated for each method using the Geomorph package in R (Adams and Otárola-Castillo, 2013).…”
Section: Biology Open • Accepted Manuscriptmentioning
confidence: 99%
“…Atlas-based approaches estimate an unbiased anatomical ‘template’ from a group of images ( Guimond et al, 2006 ) and then use this template as the basis to assess shape differences among groups of interest ( Ashburner and Friston, 2000 ). Atlas-based approaches have been used to characterize phenotypes in many neuroimaging studies in humans and fetal mice ( Mandal et al, 2012 ; Mazziotta et al, 2001 ; KOMP2 project), as well as in the cranial skeleton of humans and mice ( Darvann et al, 2011 ; Maga et al, 2017 ; Toussaint et al, 2021 ). We define pseudo-landmarks here as landmarks that are not morphologically homologous, but instead, are placed automatically on the surface of the template and transferred to each specimen, enforcing a degree of geometric homology.…”
Section: Introductionmentioning
confidence: 99%
“…Landmarks" section. The segmentations may further be used for surface-based analyses 58 , measures of size (e.g., volume or surface), or as masks to reduce the shape dimensionality of a voxel-based morphometry analysis. Unlike the adult atlas, the embryo atlases do not come with segmentations due to the scope of this work, apart from the pre-existing E15.5 atlas, which has 48 manually segmented structures (http://www.mouseimaging.ca/technologies/mouse_atlas/mouse_embryo_atlas.html).…”
Section: Reference Atlasesmentioning
confidence: 99%